Combination of PD-1/PD-L1 and CTLA-4 inhibitors in the treatment of cancer – a brief update - Park, Johan; Skålhegg, Bjørn Steen (Frontiers in Immunology, 2025)
The introduction of immune checkpoint inhibitors (ICIs) has revolutionized cancer therapy, offering durable responses in multiple malignancies by targeting regulatory pathways such as programmed cell death protein 1 (PD-1), its ligand (PD-L1), and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4). These pathways, which normally maintain immune tolerance and homeostasis, can be exploited by tumors to evade immune surveillance. Dual blockade using monoclonal antibodies (mAbs) targeting PD-1/PD-L1 and CTLA-4 has shown synergistic effects, improving response rates, overall survival, and progression-free survival in several cancer types. The U.S. Food and Drug Administration (FDA) has approved two such combinations: nivolumab plus ipilimumab and durvalumab plus tremelimumab, based on demonstrated clinical benefit in melanoma, renal cell carcinoma, colorectal cancer, hepatocellular carcinoma, non-small cell lung cancer, pleural mesothelioma, and esophageal squamous cell carcinoma. However, clinical benefit has not been consistent across all tumor types, with limited efficacy observed in cancers such as glioblastoma, head and neck squamous cell carcinoma, and Merkel cell carcinoma. Additionally, combination therapy is associated with a higher incidence of immune-related adverse events, affecting multiple organ systems and necessitating careful dosing strategies to balance efficacy and toxicity. This review summarizes the current landscape of FDA-approved PD-1/PD-L1 and CTLA-4 combinations, their therapeutic achievements, clinical limitations, and supports future research in combination immunotherapy.